New composition of tungsten has a broad range of antiviral activity. (April 2022) - Avagyan, Hranush; Mirzoyan, Anaida; Mirzoyan, Ferdinand; Izmailyan, Roza; Hakobyan, Sona; Voskanyan, Henry; Semerjyan, Zara; Avetisyan, Aida; Arzumanyan, Hranush; Karalova, Elena; Abroyan, Liana; Hakobyan, Lina; et al.
The water-based combination of two inorganic chemical compounds such as sodium tungstate dihydrate-Na2 WO4 × 2H2 O and Aluminum sulfate octadecahydrate-Al2 (SO4 ) 3 × 18H2 O that we have conditionally named 'Vomifal' has a broad antiviral activity in various DNA and RNA viruses, including Human Herpes Virus (HHV), African Swine Fever Virus (ASFV), Vaccinia Virus (VV), Hepatitis C Virus (HCV), Foot and Mouth Disease Virus (FMDV), Influenza A virus (A/Aichi/2/68 (H3N2)). In vitro and In vivo assays in several tissue cultures as well as in laboratory animals, conformed 'Vomifal' has a very low toxicity and the antiviral properties partially are due to its ability to induce gamma-IFN. Based on the results obtained, we can assume the presence of at least two mechanisms of the antiviral action of the studied drug. First or early stage - an unknown mechanism, possibly related to the effect on cellular receptors. Second or late stage – main antiviral properties probably associated with an interferonogenic effect.